(untitled) (Research, Society and Development, 2021)
Milk and dairy products are foods more susceptible to suffer attacks from microorganisms. The inspection of these foods in Brazil is made by the Municipal, State or Federal inspectors and this verification of the hygienic-sanitary quality is an extremely important activity. Microbiological contamination during the food process increases the risk of foodborne cross-contamination diseases. Therefore, the safety in the production, packaging and storage of cheeses can be verified by evaluating the microbiological quality. This article proposes a systematic review of the microbiological parameters of cheeses produced and sold in Brazil and the analysis of their microbiological quality. In order to accomplish this review, we based on different articles published from January 2014 to august 2021 and found on Academic Google platform, Scielo and CAPES periodicals. According to the analysis, we found that, in primary parameters, there is a direct correlation between good hygiene practices in the correct handling of raw materials and application of sanitary norms resulting in a lower microbiological load present in the samples. In this way, the efficiency of the implementation of correct hygiene practices promotes a reduction in the risk of foodborne outbreaks. Finally, we note which in spite of the existence of bacterial flora, the presence of external pathogens is a major problem.